INTRODUCTION TO CORN CROP (Zea mays Saccharata L.) PRODUCING BABY CORN AND FORAGE WITH VARIETIES AND HARVEST AGES IN CILELES VILLAGE, JATINANGOR DISTRICT, SUMEDANG REGENCY - Nyimas Popi Indriani; Heryawan Kemal Mustafa; Romi Zamhir Islami (Media Kontak Tani Ternak, 2022)
ABSTRACT The community service in Cileles Village aimed to increase insight through the knowledge and skills of farmers/breeders (Al Hikmah farmer group) about the use of corn plants as superior quality forage. The activity was carried out on Tuesday 19 July 2022 at Madrasah Al Hikmah RW 06 Cileles Village, Jatinangor District, Sumedang Regency. Community service was carried out using participatory empowerment methods which included counseling, mentoring and material assistance which actively involved the participation of the community in general and breeders in particular. The series of activities included: land preparation, planting and maintenance of corn plants. The corn used was a hybrid of various varieties of sweet corn (F1 Bonanza, F1 Janisa, F1Asia 86 and Sweet Lady). The corn seeds was planted in demonstration plots with a spacing of 70 cm x 20 cm. The conclusion from Community Service was that farmers/breeders became understand about the corn plants (Zea mays Saccharata L.) which produce baby corn and forage feed with various varieties and harvest ages. Farmers/breeders have planted the corn on the Al Hikmah farmer group’s fields.Keywords: Babycorn, forage,varieties, harvest ages